Effects of moderate red wine on cardiovascular risk factors in diabetics: a systematic review and meta-analysis of randomized controlled trials. Issue 6 (12th November 2019) - Naame, Saavia Alice; Li, Decheng; Huang, Ruixue
Graphical Abstract: Abstract: Background : Diabetes mellitus is of major public health concerns; its incidence is continuously increasing. Diabetes mellitus is associated with a high risk of cardiovascular complications such as hypertension. Red wine has been reported to reduce cardiovascular risk factors. We quantified the effects of red wine on cardiovascular factors. Methods : We retrieved English-language articles published from January 1990 to April 2019. Cardiovascular risk factors were compared using means with 95% confidence intervals (95% CIs). Results : We identified five eligible randomized controlled trials. Diabetic patients who drank red wine exhibited significantly reduced systolic blood pressure (BP) (mean difference [MD] −1.33, 95% CI −1.81, −0.85) and diastolic BP (MD −1.31, 95% CI −1.80, −0.83) than those who did not. Compared to the observations for diabetics who did not drink red wine, the high-density lipoprotein (HDL) level was significantly higher in red wine drinkers (MD −0.24, 95% CI −0.39, −0.09). However, red wine had no effect on the body mass index (BMI) (MD −0.27, 95% CI −1.80, 1.25), the total cholesterol level (MD 0.13, 95% CI −0.17, 0.44), or the low-density lipoprotein (LDL) level (MD 0.08, 95% CI −0.21, 0.37). Conclusions : Red wine consumption significantly lowered BP and increased the HDL level in diabetics. Red wine had no significant effect on BMI or cholesterol and LDL levels. Given the heterogeneity of the studied populations and the lack of standardization and completeness across the published studies, caution is required while interpreting these findings.